Innovation in Supply Chain Management and Its Financing as a Factor of Economic Growth - Nadezhda N. Semenova; Tatyana V. Ermoshina; Olga I. Eremina; Irina B. Yulenkova (International Journal of Supply Chain Management, 2019)
Abstract- Innovation in supply chain is becoming an increasingly significant factor in the socio-economic development of national economies these days. Continuous innovation plays a crucial role in increasing the competitiveness of social production, profits made by economic entities, economic growth, and, consequently, the national economy. Innovative development cannot occur without the presence of effective mechanisms for financing innovation. The purpose of this study is to assess the impact of innovation and its financing on the economic growth of the Republic of Mordovia – one of the federal subjects of the Russian Federation. The authors conducted a correlation and regression analysis to determine the influence of factors related to innovative development on the volume of the Gross Regional Product (GRP). This method allows identifying key factors influencing the rate of economic growth in the region, as well as to build a forecast of the future GRP. Empirical results indicate that the GRP of the Republic of Mordovia is greatly influenced by the financing of research and development (R & D). The resulting regression equation indicates that the 92% change in the GRP is due to the R & D expenditures, and 8% – the influence of other factors. It was also found that the increase in domestic R & D costs by 1 million rubles results in an increase in the GRP by an average of 200 million rubles. The results indicate that it is necessary to increase R& D financing, provided that its growth is balanced at different stages of innovation.